Cracking in concrete near joints in steel-concrete composite slab = Zarysowanie płyty żelbetowej w strefie przywęzłowej stropu zespolonego - Niedośpiał, Marcin; Knauff, Michał; Barcewicz, Wioleta (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In this paper results of the experimental tests of four full-scale composite steel-concrete elements are reported. In the steel-concrete composite elements, a steel beam was connected with a slab cast on profiled sheeting, by shear studs.
Keywords: zarysowanie; strop zespolony; węzły podatne; cracking; steel-concrete composite slab; semi-rigid joints